2022
DOI: 10.1002/jum.16060
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of the Width of the Four‐Chamber View and the Area, Length, and Width of the Ventricles to Identify Fetuses at High‐Risk for D‐Transposition of the Great Arteries and Tetralogy of Fallot

Abstract: Objectives The prenatal detection of D‐Transposition of the great arteries (D‐TGA) and tetralogy of Fallot (TOF) has been reported to be less than 50% to as high as 77% when adding the outflow tracts to the four‐chamber screening protocol. Because many examiners still struggle with the outflow tract examination, this study evaluated whether changes in the size and shape of the heart in the 4CV as well as the ventricles occurred in fetuses with D‐TGA and TOF could be used to screen for these malformations. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…It is known that in various disease states, the fetal heart not only increases the thickness of the ventricles and septum but also adapts by changing the size of the atria and ventricles [ 10 ]. The global spherical index (GSI) has been identified as an indicator of this change in cardiac shape [ 18 ]. The GSI is calculated by measuring the basal-apical length (BAL) and transverse length (TL) in a four-chamber view during the end diastole period.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that in various disease states, the fetal heart not only increases the thickness of the ventricles and septum but also adapts by changing the size of the atria and ventricles [ 10 ]. The global spherical index (GSI) has been identified as an indicator of this change in cardiac shape [ 18 ]. The GSI is calculated by measuring the basal-apical length (BAL) and transverse length (TL) in a four-chamber view during the end diastole period.…”
Section: Discussionmentioning
confidence: 99%
“…In 2023, using a similar theme of measuring the size and shape of the ventricular chambers, our group analyzed 88 fetuses, 44 with tetralogy of Fallot and 44 with D-TGA, to determine if measurements of the 4CV and ventricles could identify fetuses at risk for either tetralogy of Fallot or D-transposition. 22 The analysis, using logistic regression analysis, identified eight end-diastolic measurements (4CV width, RV and LV area, RV and LV length, RV width at the base (Segment 1), and the RV and LV mid-chamber width (Figure 12). From these measurements, the RV base sphericity index and the RV and LV mid-chamber sphericity index were computed (Figure 12).…”
Section: Speckle Tracking Analysis Used To Simultaneously Screen Fetu...mentioning
confidence: 99%
“…22. 93.2%, with a FPR of 6.8%. 22 The benefit of this approach was that from eight simple end-diastolic measurements of the 4CV and ventricles, the probability of either tetralogy of Fallot or Dtransposition could be quickly ascertained, prompting a re-review of the outflow tract examination if either of these two malformations were not identified during the screening examination of the fetal heart. Supplement 4 is a calculator to predict the probability of either tetralogy of Fallot or D-transposition using the measurements from…”
Section: F I G U R E 1mentioning
confidence: 99%
See 2 more Smart Citations